Intergenerational Learning – Children Singing Along with Older People – Possibilities and Complications in a Project Context - Nilsson, Lena; Herrman, Margaretha (Advances in Social Sciences Research Journal, 2016)
Culture for Older People is a project funded by Swedish Arts Council. The aim of the project, managed by heads of department’s för the preschool, the older care and the culture school, is increased well-being for older people. In this article one of the activities, Children Singing Along with Older People is scrutinised in an ongoing evaluation. In this subproject, headed by expert music teachers together with preschool teachers and care home staff, five-year old preschoolers visit care homes for singing along with the residents. The project is poly-motivated; besides improved well-being for older people, also enhanced learning for the children and interprofessional learning for staff. The concept musicking, which highlights music as an activity creating community and relations between participators, is used for discussing the meetings between the children and older people. Results are based on observations of activities and interviews with staff. Music is an activity that can be used for enhanced well-being and creating relations as well as learning. Nonetheless there are issues in the project that need to be discussed e. g. children’s participation and role, the older’s activity or desire for passivity and support for learning among the staff as well among children and older.